Producción científica en Colombia relacionada con ciencia abierta, métricas de nueva generación y métricas responsables en el contexto de Publindex y SCIENTI: Algunas características y perspectivas para apoyar una Política Nacional - Uribe-Tirado, Alejandro; Vélez-Cuartas, Gabriel-Jaime; Pallares-Delgado, Cesar-Orlando (Revista Científica, 2023)
This article presents a topic review on the publications by Colombian authors in recent years with regard to open science, new-generation metrics (altmetrics), and responsible metrics, in contextual interrelation with the country’s practices for evaluating and measuring scientific journals (Publindex) and research groups and researchers (SCIENTI), considering the changes implied by the recently approved National Open Science Policy. The list of texts, selected via qualitative analysis, is an important input in the discussions and new constructions around said National Policy, in order for the assessment, recognition, and evaluation of activities involving science, technology, and innovation in the country to include responsible metrics and alternative open science indicators aimed at assessing the diversity of the products and processes carried out, as well as the different economic, social, and territorial impacts caused by these practices.